2022
DOI: 10.3389/fenvs.2022.998513
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns of microplastics in subtidal sediments from the Sado river estuary and the Arrábida marine park, Portugal

Abstract: Understanding local accumulation patterns of microplastics in subtidal sediments is crucial to assess how available such particles are for ingestion by benthic feeders and to identify the potential pollution sources in the region upon which is urgent to act. The coastal urban centers of Setúbal and Sesimbra (Portugal) and the multiple activities taking place at the contiguous Sado estuary and in the sheltered waters of Professor Luiz Saldanha Marine Park make this a relevant case study about MPs pollution in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 138 publications
2
8
0
Order By: Relevance
“…The prevalence of PE, PP and PS polymers in Yarkon, is in line with reports from the Ionian, Aegean, and Levantine Seas (Adamopoulou et al, 2021), central Mediterranean Sea (Marrone et al, 2021) and other Mediterranean Sea studies (Suaria et al, 2016;Sharma et al, 2021). Similar to Yarkon, PE and PP polymers were also the most common in Sado, which agrees with studies in Arrábida and Setúbal (Rodrigues et al, 2022). The plastic polymer type is not considered a major factor that is affecting the plastisphere microbiome in the natural environment (Oberbeckmann et al, 2018;Laverty et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The prevalence of PE, PP and PS polymers in Yarkon, is in line with reports from the Ionian, Aegean, and Levantine Seas (Adamopoulou et al, 2021), central Mediterranean Sea (Marrone et al, 2021) and other Mediterranean Sea studies (Suaria et al, 2016;Sharma et al, 2021). Similar to Yarkon, PE and PP polymers were also the most common in Sado, which agrees with studies in Arrábida and Setúbal (Rodrigues et al, 2022). The plastic polymer type is not considered a major factor that is affecting the plastisphere microbiome in the natural environment (Oberbeckmann et al, 2018;Laverty et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…The high percentage of films documented in the winter (37.78%), can be explained by the faster degradation of plastic bags and packaging, which is considered their main source (Marrone et al, 2021). The same was observed for Sado, where fragments predominated during summer (63.49%) and winter (76.34%), which is in agreement with samples from the North East Atlantic (63%) and from Arrábida and Setúbal (Rodrigues et al, 2022).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The samples can be preserved by refrigeration, the use of a suitable sample container, or the addition of preservative chemicals [55]. The samples are usually stored in a refrigerator at 4 • C [56] or deepfrozen at below −20 • C [57] until they are analysed. In some cases, the identification and characterisation of the biological substance may be relevant for other aspects of the research, which is why different fixation solutions are used (70-80% ethanol [58] or 4-5% formalin [59]).…”
Section: Challenges In the Analysis Of Microplastic Particles In Envi...mentioning
confidence: 99%
“…So far, the pore sizes used in different studies have not been standardised, so the amount of MPs found varies, making it impossible to compare the results (Figure 4). [86], [80], [87], [88], [89], [88], [57].…”
Section: Sampling Strategies For Wastewater Samplesmentioning
confidence: 99%